Evening dosing versus morning dosing of antihypertensive medications for nocturnal hypertension: a systematic review and meta-analysis of 107 randomized controlled trials - Lee, Eric Kam-Pui; Wang, S; Ng, W. L.; Ramdzan, S. N; Tse, E. T. Y; Chan, L; Rashid, A. A; Chin, W. Y; Yu, C. P; Sit, R; Poon, P (Lippincott Williams and Wilkins, 2024)
Objective: Since the effects of once-daily antihypertensive (HT) medications are more pronounced within the first few hours of ingestion, evening administration of anti-HT medications can be a feasible treatment for nocturnal HT. However, no relevant meta-analysis has been conducted in patients with nocturnal HT. Methods: This meta-analysis included randomized controlled trials involving patients with elevated mean nocturnal blood pressure (BP) and compared evening anti- HT administration with morning administration. Multiple databases, including grey literature (e.g. clincialtrial.gov), were searched. Study selection and data extraction were conducted by two independent authors. Risk of bias assessment and overall quality of evidence were conducted using Cochrane risk-of-bias tool and GRADE by two independent authors. Results: A total of 107 studies were included, 76 of which were investigated in China and had not been identified in previous reviews. Only one trial was ranked low risk-ofbias. Evening administration of anti-HT medications was effective in reducing nocturnal systolic BP (4.12–9.10 mmHg; I2¼80.5–95.2%) and diastolic BP (3.38–5.87 mmHg; I2¼87.4–95.6%). Subgroup analyses found that the effectiveness of evening administration was contributed by data from the Hermida group and China. Evening administration did not provide additional nocturnal/daytime/24-h BP reduction in non-Hermida/non- China studies (I2¼0) and in meta-analyses that included studies with unclear or low risk of bias. The effectiveness of nocturnal BP reduction was similar across different types, doses, and half-lives of medications. Evening administration of anti-HT medications may reduce proteinuria, left ventricular hypertrophy (LVH), nondipping and morning surge. The overall quality of evidence was ranked as very low to low. Conclusion: Our results highlight the scarcity of low riskof- bias studies and emphasize the need for such trials to evaluate the efficacy of evening dosing of anti-HT medications as a standard treatment for patients with nocturnal HT across diverse populations.